2016
DOI: 10.1111/jdi.12584
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the association between glucose profiles and β‐cell function for diabetic cardiovascular autonomic neuropathy in China

Abstract: Aims/IntroductionThe purpose of the present study was to investigate the severity of glucose profiles and β‐cell function associated with diabetic cardiovascular autonomic neuropathy (DCAN) in a Chinese sample.Materials and MethodsA community‐based, cross‐sectional study to analyze the risk factors of DCAN was carried out with 455 individuals recruited from a Chinese population. The glucose profile risk score was calculated to identify the association between the severity of the glucose profiles and DCAN. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…As was discussed in earlier studies [ 25 27 ], ULR analysis showed associated factors for DCAN, including age, BMI, FPG, PBG, FINS, TG, resting HR, DM duration, HTN duration, and MetS (P<0.05 for all). The simple association factors of age, BMI, DM duration, and HR were included in the final MLR model (P<0.05 for all; Table 2 ).…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…As was discussed in earlier studies [ 25 27 ], ULR analysis showed associated factors for DCAN, including age, BMI, FPG, PBG, FINS, TG, resting HR, DM duration, HTN duration, and MetS (P<0.05 for all). The simple association factors of age, BMI, DM duration, and HR were included in the final MLR model (P<0.05 for all; Table 2 ).…”
Section: Resultssupporting
confidence: 65%
“…As we discussed in an earlier study [ 25 , 26 , 29 ], short-term HRV tests can be used for the evaluation of cardiovascular autonomic function, and we used short-term HRV tests in this study. The protocol for the short-term HRV test was detailed earlier [ 25 27 ]. The definition of DCAN was based on at least 2 abnormal results from cardiovascular autonomic function testing [ 4 , 25 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously developed clinical risk models for predicting CAN in a general Chinese population. 10 Our findings indicated that glucose profiles, lipid profiles, and blood pressure (BP) profiles were significantly associated with DCAN, [11][12][13] suggesting that these factors may predict the development of DCAN in diabetes patients. Additionally, a screen model with high sensitivity and specificity for DCAN had been developed.…”
Section: Introductionmentioning
confidence: 77%
“…As is mentioned in our previous studies, [11][12][13][14] a DCAN risk factor analysis in a Chinese random sample was carried out using established methods. Diabetic participants aged 30-80 years with undiagnosed CAN were recruited from rural and urban communities in Shanghai.…”
Section: Study Populationmentioning
confidence: 99%